Click for Tolerance: The Transformation of Christian Religious Education through Digital Media in Fostering Inclusive Attitudes in Indonesia - Bulan, Susanti Embong; Simangunsong, Amran (MODERATE: Journal of Religious, Education, and Social, 2025)
This study examines the transformation of Christian Religious Education (CRE) in Indonesia through the integration of digital media as a pedagogical and theological tool for nurturing inclusivity and tolerance in a plural society. Employing a qualitative–interpretive approach, the research combined semi-structured interviews, document analysis, and digital ethnography involving Christian educators, students, and online learning communities. This design allowed the study to capture how digital platforms influence religious formation, interfaith engagement, and ethical awareness within virtual learning environments. The findings indicate that digital media can democratize access to theological education and foster intercultural dialogue by creating new spaces of communication and collaboration. However, challenges emerge in the form of digital alienation, ethical ambiguity, and the risk of superficial spiritual engagement. Through a critical–reflective framework, the study argues that the effectiveness of digital Christian education depends on its ability to integrate technological innovation with moral discernment and theological depth. The research concludes that inclusivity in digital pedagogy is not merely a technical or institutional concern but a spiritual and ethical endeavor grounded in love, justice, and respect for human dignity. Ultimately, this study proposes a vision of “clicking for tolerance”—a model of Christian education that transforms digital spaces into environments of dialogue, compassion, and peace, contributing to Indonesia’s broader project of interreligious harmony.   Contribution: This study contributes to the development of digital theology and Christian Religious Education by offering a reflective framework for integrating faith, ethics, and technology in Indonesia’s pluralistic context. It provides practical insights for educators and policymakers on how digital platforms can become instruments of inclusion, empathy, and peacebuilding through faith-informed pedagogy.   Penelitian ini mengkaji transformasi Pendidikan Agama Kristen (PAK) di Indonesia melalui integrasi media digital sebagai alat pedagogis dan teologis untuk menumbuhkan sikap inklusif dan toleransi dalam masyarakat yang majemuk. Dengan menggunakan pendekatan kualitatif–interpretatif, penelitian ini menggabungkan wawancara semi-terstruktur, analisis dokumen, dan etnografi digital yang melibatkan para pendidik Kristen, siswa, serta komunitas pembelajaran daring. Desain ini memungkinkan penelitian untuk menangkap bagaimana platform digital memengaruhi pembentukan religius, keterlibatan lintas iman, dan kesadaran etis dalam lingkungan pembelajaran virtual. Temuan menunjukkan bahwa media digital dapat mendemokratisasi akses terhadap pendidikan teologis dan mendorong dialog antarbudaya melalui penciptaan ruang-ruang komunikasi dan kolaborasi baru. Namun, tantangan muncul dalam bentuk keterasingan digital, ambiguitas etika, serta risiko keterlibatan spiritual yang dangkal. Melalui kerangka kritis–reflektif, penelitian ini berpendapat bahwa efektivitas pendidikan Kristen digital bergantung pada kemampuannya untuk mengintegrasikan inovasi teknologi dengan kepekaan moral dan kedalaman teologis. Penelitian ini menyimpulkan bahwa inklusivitas dalam pedagogi digital bukan sekadar persoalan teknis atau kelembagaan, tetapi merupakan upaya spiritual dan etis yang berakar pada kasih, keadilan, dan penghormatan terhadap martabat manusia. Pada akhirnya, penelitian ini mengajukan visi “klik untuk toleransi” — sebuah model pendidikan Kristen yang mentransformasi ruang digital menjadi lingkungan dialog, belas kasih, dan perdamaian, serta berkontribusi pada proyek besar harmoni antaragama di Indonesia.   Kontribusi: Studi ini berkontribusi terhadap pengembangan teologi digital dan Pendidikan Agama Kristen dengan menawarkan kerangka reflektif untuk mengintegrasikan iman, etika, dan teknologi dalam konteks pluralistik Indonesia. Studi ini memberikan wawasan praktis bagi para pendidik dan pembuat kebijakan tentang bagaimana platform digital dapat menjadi sarana inklusi, empati, dan pembangunan perdamaian melalui pedagogi yang berlandaskan iman.